2014
DOI: 10.1182/blood.v124.21.2888.2888
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Platelet Transfusion Increases Platelet Increment in Refractory Hemato-Oncological Patients – a Single Center Experience

Abstract: Background: Refractoriness to platelet transfusion is prevalent among 15-25% of hemato-oncology patients. Refractoriness has been linked to inferior clinical outcomes, including bleeding and mortality, as well as higher health care costs. Suggested etiologies to refractoriness include both non-immune and immune causes. Methods to manage refractoriness include leuko-reduction, HLA- and HPA- matched platelets, use of ABO compatible transfusions and platelet cross-matching. Leuko-reduction has been proven to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[ 2 ] In Tzadok et al . and extended small dose platelet transfusion group, patients received a continuous 24 h SDP transfusion with each dose comprising 1.5 × 10 11 platelets given over 4 to 6 h.[ 3 6 ] In the present patient, double dose SDP was divided into six aliquots with 1 × 10 11 platelets in each aliquot transfused over 4 h in closed system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 2 ] In Tzadok et al . and extended small dose platelet transfusion group, patients received a continuous 24 h SDP transfusion with each dose comprising 1.5 × 10 11 platelets given over 4 to 6 h.[ 3 6 ] In the present patient, double dose SDP was divided into six aliquots with 1 × 10 11 platelets in each aliquot transfused over 4 h in closed system.…”
Section: Discussionmentioning
confidence: 99%
“…When patients with PTR have no HLA/HPA-compatible platelet donors or in the setting of ongoing bleeding, massive platelet transfusion, and continuous platelet transfusion commonly known as “platelet drips” were attempted with varied results. [ 2 3 6 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of multivariate logistic regression analysis in this study showed that transfusion frequency was not considered as a risk factor for ineffective transfusion, it was speculated that the transfusion of platelet samples and the interval time between transfusions in this study might have influenced the results. Previous studies (27) have shown that with the increase of transfusion times, platelet antibodies will develop in patients, hindering the efficacy of platelet transfusion. The results may be different from the effect of transfusion on the number of transfusion in patients with different physical conditions.…”
Section: Discussionmentioning
confidence: 99%